Charge Transfer Parameters of NixMnyCo1−x−y Cathodes Evaluated by a Transmission Line Modeling Approach. Issue 6 (15th January 2021) - Costard, Janina; Joos, Jochen; Schmidt, Adrian; Ivers-Tiffée, Ellen
Abstract : The performance of lithium‐ion batteries can be analyzed and improved by appropriate electrochemical models. A challenging yet crucial part is the parameterization of these models. Until now, the literature has incompletely investigated and cited the charge transfer process parameters describing the lithium transfer between the active material particles in the electrode and the liquid electrolyte. Herein, a novel approach is presented for obtaining these charge transfer parameters. The well‐established experimental methods of electrochemical impedance spectroscopy and focused ion beam tomography are applied. By introducing both experimental results into a transmission line model, a reliable determination of the charge transfer parameters j 0, k, and r CT can be achieved. The new approach is validated by comparing the results of four cathodes, all containing the state‐of‐the‐art active material Ni x Mn y Co1− x − y (NMC), but with different microstructures and/or stoichiometries. Abstract : Herein, a new approach for obtaining the exchange current density i 0, exchange coefficient k, and area‐specific charge transfer resistance r CT of lithium‐ion‐battery cathodes is reported. Necessary model parameters are experimentally determined by electrochemical impedance spectroscopy (EIS), focused ion beam (FIB)/scanning electron microscopy (SEM) tomography, and conductivity measurements and utilized in a transmission line model (TLM) for porous electrode structures.